The Bioethical Aspects in the Cancer Patients Treated by Means of Clinical Trials in Cuba (Revista Iberoamericana de Bioética, 2019)
The bioethical aspects in clinical trials are regulated by organizations such as the FDA, the European Agency and, in Cuba, the Centro Nacional Coordinador de Ensayos Clínicos. The aim of this paper is to determine the importance of codes, guidelines and regulations for the safety and well-being of the subject of the trial. As a method, the review of the issue on the databases Medline, Hinari, Scielo, Springer, Wiley and others on the webpage http://www.infomed.sld.cu were used. In conclusion, the codes, guidelines and regulations for the safety and well-being of the subject of the trial were analysed in order for cancer patients to be treated ethically and not as means or objects.
Keywords: neoplasms; treatment; clinical trials; investigations; selection of subjects; regulatory agencies; clinical studies; health services; biological drugs